The Effect Of Promotion, Price, And Brand Image On Purchase Decisions On E-Commerce Shopee In Pangkalpinang City - Afrizal Afrizal; Fithriawan Nugroho (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study is a quantitative study that aims to determine the effect of promotion, price, and brand image on purchasing decisions at Shopee e-commerce in Pangkalpinang City. The population in this study are Shopee users who make purchases in Pangkalpinang City with a sample of 75 respondents using the non-probability sampling method with purposive sampling technique. Hypothesis testing in this study uses Partial Least Square (PLS) analysis tool and a significance level of 5%. The results of this study were obtained (promotion has a significant effect on purchasing decisions, price has no significant effect on purchasing decisions, brand image has a significant effect on purchasing decisions.